The Meaningful Involvement of People with HIV/AIDS (MIPA): The Participatory Praxis Approach to Community Engagement on HIV Surveillance - Andrew Spieldenner; Martin French; Venita Ray; Brian Minalga; Cristine Sardina; Robert Suttle; Marco Castro-Bojorquez; Octavia Lewis; Laurel Sprague (The University of Alabama, 2022)
The Meaningful Involvement of People with HIV/AIDS (MIPA) has been at the core of the HIV response since the beginning of the HIV epidemic. In this study, we compare two community engagement activities concerned with molecular HIV surveillance (MHS) in the United States: one governmental and one community-led. We examine the consultative aspects of each one, especially as they relate to people living with HIV. We point to the community-based effort-which used a participatory praxis approach-as an example of MIPA. We derive two best practice principles from this research from the field.